Validity and Reliability of the Persian Version of the Sports Nutritional Knowledge, Attitudes, Behaviors questionnaire in Adolescent Athletes - Faezeh Ahmadi; Mohsen Ebrahimi; Valiolah Kashani (Journal of Fasting and Health, 2021)
Introduction: The present study aimed to evaluate the validity and reliability of the Persian version of the Sports Nutritional Knowledge, Attitudes, Behaviors questionnaire (SNKABQ) in adolescent athletes. Methods: SNKABQ was designed by Walsh et al. The questionnaire was translated and re-translated using the WHO standard method and in line with the Iranian culture and nutrition habits. The qualitative content validity of the questionnaire was assessed by five experts, time reliability was assessed using the test-retest method, and the correlation coefficient and differential validity were determined by comparing novice and skilled athletes using the Mann-Whitney U test. In addition, the internal consistency of the questionnaire was assessed based on Cronbach's alpha, and the questionnaire was completed by 191 male and female students aged 15-18 years. Results: The total time reliability of the questionnaire was estimated at 0.86, while it was 0.92 for eating and drinking habits, 0.75 for nutrition attitudes, 0.88 for nutrition knowledge, and 0.89 for nutrition information sources. Moreover, the Mann-Whitney U test indicated that the questionnaire has significant differential validity (P=0.00). The total internal reliability of the questionnaire was determined to be 0.74. The internal reliability of the subscales was also measured and estimated at 0.71 for eating and drinking habits, 0.80 for nutrition attitudes, and 0.70 for nutrition knowledge and nutrition information sources. Conclusion: SNKABQ had acceptable validity and reliability in the adolescent athletes and could be used as a tool for the assessment of Iranian adolescent athletes.